Environmentally friendly stabilizer for PVC foam products and preparation method thereof

By using zinc salt, calcium salt, zinc oxide-mannitol composite materials and environmentally friendly stabilizers coupled with graft modified water-calciumite in PVC foaming materials, the local overheating and uneven foaming problems caused by the rapid decomposition rate of azodicarbonate amine is solved, and the efficient thermal stability and compatibility of PVC foamed products are achieved.

CN119410086BActive Publication Date: 2025-04-29SHANDONG JINCHANGSHU NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510030998.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-29
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The azodicarboxylate used in the preparation process of existing PVC foaming materials is used as the foaming agent, and the decomposition speed is too fast, resulting in local overheating and sudden deflation, resulting in uneven foaming and decomposition of PVC substrates, which improves the performance requirements for heat stabilizers.

Method used

The environmentally friendly stabilizer including zinc salt main stabilizer, calcium salt main stabilizer, zinc oxide-mannitol composite material and coupled grafted modified water-aluminum calcium is used to improve the initial coloring properties of PVC through zinc oxide-mannitol composite material, and absorb the released HCl by the heat drop of PVC by coupling grafted modified water-aluminum calcium to prevent high-temperature decomposition of PVC.

Benefits of technology

It effectively reduces the decomposition temperature of azodicarboxylate, prevents high-temperature decomposition of PVC substrates, improves the thermal stability and compatibility of PVC foamed products, and improves foaming uniformity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410086B_ABST
    Figure CN119410086B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polymer materials, and specifically relates to an environmentally friendly stabilizer for PVC foam products and a preparation method thereof, and comprises the following components by weight: 10-12 parts of a zinc salt main stabilizer, 38-42 parts of a calcium salt main stabilizer, 13-16 parts of a zinc oxide-mannitol composite material, and 32-35 parts of a coupled grafted modified hydrocalumite. The environmentally friendly stabilizer prepared by the present invention can improve the initial coloring and long-term thermal stability of PVC, while being able to alleviate the local overheating phenomenon produced by azodicarbonamide as a foaming agent, and preventing the PVC substrate from being decomposed at high temperature, and the coupled grafted modified hydrocalumite used contains both a polar aluminate group and a non-polar long-chain alkyl group, which can weaken the cohesive force between PVC macromolecules, reduce the PVC melt viscosity, and improve the fluidity of the melt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and particularly relates to an environmentally friendly stabilizer for PVC foam products and a preparation method thereof. Background Art

[0002] Since the end of the 20th century, my country's foam plastic industry has developed rapidly. The representative varieties are mainly polystyrene foam plastic, polyurethane foam plastic and polyethylene foam plastic. However, the above three types of foam plastics have a common limitation, that is, they are easy to burn. In order to change the defect of foam plastics being flammable, PVC foam plastic came into being. Compared with other foam plastics, PVC foam plastic itself has better flame retardancy and is widely used in furniture, construction, automobiles, advertising, decoration and other industries. It has developed rapidly in recent years.

[0003] During the preparation process of PVC foam materials, foaming agents, heat stabilizers, nucleating agents, etc. need to be added. Existing PVC foam materials generally use azodicarbonamide as a foaming agent. However, since azodicarbonamide is a highly exothermic foaming agent, excessive decomposition speed will cause local overheating and sudden gas release, which will not only cause uneven foaming, but also cause decomposition of the PVC substrate. This places higher performance requirements on the heat stabilizer used in PVC foam materials. Summary of the invention

[0004] The object of the present invention is to provide an environmentally friendly stabilizer for PVC foam products and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] In order to achieve the above technical objectives, the technical solution of the present invention is:

[0006] The environmentally friendly stabilizer for PVC foam products comprises the following components by weight: 10-12 parts of zinc salt main stabilizer, 38-42 parts of calcium salt main stabilizer, 13-16 parts of zinc oxide-mannitol composite material, and 32-35 parts of coupled grafted modified hydrocalumite.

[0007] As a further improvement, the following components are included by weight: 11.4 parts of zinc salt main stabilizer, 40 parts of calcium salt main stabilizer, 14.3 parts of zinc oxide-mannitol composite material, and 34.3 parts of coupled grafted modified hydrocalumite.

[0008] The calcium salt main stabilizer is calcium stearate, the zinc salt main stabilizer is zinc stearate, the zinc oxide-mannitol composite material is a complex of mannitol zinc salt, mannitol and zinc oxide, and the mass ratio of mannitol zinc salt, mannitol and zinc oxide is 37:6:7.

[0009] The present invention also provides a method for preparing an environmentally friendly stabilizer for PVC foam products, comprising the following steps:

[0010] S1. Preparation of zinc oxide-mannitol composite material;

[0011] Add zinc oxide and mannitol into a three-necked flask, heat to 200°C in a nitrogen atmosphere, stir and react for 2 hours, take out the product after cooling, and then dry the product in a vacuum oven at 70°C for 12 hours to obtain a zinc oxide-mannitol composite material;

[0012] S2. Preparation of hydrocalumite:

[0013] Calcium hydroxide, sodium aluminate and sodium carbonate are used as raw materials and hydrocalumite is prepared by a hydrothermal crystallization method.

[0014] S3, preparation of coupled grafted modified hydrocalumite;

[0015] Add an aluminate coupling agent to anhydrous ethanol and stir evenly to obtain an aluminate coupling agent solution, then add the above-prepared hydrocalumite to a beaker filled with distilled water, stir with a glass rod and drain into a three-necked flask, add the above-prepared aluminate coupling agent solution to the three-necked flask, stir in a 45°C water bath for 45 minutes, then add n-dodecene and initiator azobisisobutyronitrile to the three-necked flask, heat to 60°C, react for 3 hours, after the reaction is completed, use ethanol as a solvent, purify and extract with a Soxhlet extractor at 80°C for 24 hours, and dry at 70°C to obtain coupling grafted modified hydrocalumite;

[0016] S4. Preparation of environmentally friendly stabilizer;

[0017] The zinc salt main stabilizer, the calcium salt main stabilizer, the zinc oxide-mannitol composite material and the coupled grafted modified hydrocalumite were weighed respectively, ground and mixed for 10 minutes, and then the mixture was placed in a 120° C. oven and baked for 2 hours, and then the mixture was cooled to room temperature to obtain an environmentally friendly stabilizer.

[0018] As a further improvement, in step S1, the molar ratio of zinc oxide to mannitol is 1:1.

[0019] As a further improvement, in step S2, the specific steps of the hydrothermal crystallization method are: adding calcium hydroxide, sodium aluminate and sodium carbonate in a molar ratio of 4:2:1 to a reactor, adding 180 mL of deionized water to the reactor, and then stirring at room temperature for 10 hours, transferring it to a 180°C, 10 MPa high-pressure reactor for insulation and aging for 12 hours, then taking out the reactor and cooling it to room temperature, removing the supernatant, and then rinsing the obtained product with deionized water to neutrality and filtering it, and placing the filter cake in a vacuum drying oven at 60°C to dry it to obtain solid hydrocalumite.

[0020] As a further improvement, the amount of the aluminate coupling agent used is 7% of the mass of hydrocalumite, the mass ratio of n-dodecene to the aluminate coupling agent is 3:1, and the amount of the initiator azobisisobutyronitrile added is 2.5% of the mass of n-dodecene.

[0021] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0022] The invention provides an environmentally friendly stabilizer for PVC foam products and a preparation method thereof. The zinc oxide-mannitol composite material can be used as an environmentally friendly heat stabilizer to improve the initial colorability of PVC. On the other hand, the zinc oxide in the zinc oxide-mannitol composite material can activate azodicarboxylic acid amide and reduce the decomposition temperature of the azodicarboxylic acid amide. Meanwhile, the mannitol contained in the zinc oxide-mannitol composite material can undergo a phase change and absorb heat after reaching 160° C., thereby alleviating the local overheating phenomenon caused by the azodicarboxylic acid amide as a foaming agent and preventing the high-temperature decomposition of the PVC substrate.

[0023] The environmentally friendly stabilizer of the present invention is added with coupled grafted modified hydrocalumite. The hydrocalumite is a layered double metal hydroxide with a layered structure, can absorb and neutralize HCl released by thermal degradation of PVC, and plays a role in preventing thermal aging of PVC. However, the hydrocalumite is a polar substance and has poor compatibility with PVC. In the present invention, the coupled grafted modified hydrocalumite is modified by coupled grafting, and the polarity of the hydrocalumite is changed, so that the compatibility with PVC is good. In addition, the coupled grafted modified hydrocalumite used in the present invention contains both polar aluminate groups and non-polar long-chain alkyl groups, so that the cohesive force between PVC macromolecules can be weakened, the melt viscosity of PVC can be reduced, and the fluidity of the melt can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a graph showing the results of the melt index analysis experiment in Example 6. DETAILED DESCRIPTION

[0025] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0026] Example 1 An environmentally friendly stabilizer for PVC foam products comprises the following components by weight: 11.4 parts of a zinc salt main stabilizer, 40 parts of a calcium salt main stabilizer, 14.3 parts of a zinc oxide-mannitol composite material, and 34.3 parts of coupled grafted modified hydrocalumite.

[0027] Among them, the main calcium salt stabilizer is calcium stearate, the main zinc salt stabilizer is zinc stearate, the zinc oxide-mannitol composite material is a complex of mannitol zinc salt, mannitol and zinc oxide, and the mass ratio of mannitol zinc salt, mannitol and zinc oxide is 37:6:7.

[0028] This embodiment also provides a method for preparing the above-mentioned environmentally friendly stabilizer, comprising the following steps:

[0029] S1. Preparation of zinc oxide-mannitol composite material;

[0030] 8.14 g of zinc oxide and 18.22 g of mannitol were added into a three-necked flask, heated to 200° C. in a nitrogen atmosphere, stirred for reaction for 2 h, and the product was taken out after cooling, and then the product was dried in a vacuum oven at 70° C. for 12 h to obtain a zinc oxide-mannitol composite material, wherein the molar ratio of zinc oxide to mannitol was 1:1;

[0031] S2. Preparation of hydrocalumite:

[0032] Calcium hydroxide, sodium aluminate and sodium carbonate are used as raw materials, and hydrocalumite is prepared by a hydrothermal crystallization method, specifically: 29.64g of calcium hydroxide, 16.6g of sodium aluminate and 10.6g of sodium carbonate are added to a reactor, 180mL of deionized water is added to the reactor, and then stirred at room temperature for 10 hours, and then transferred to a high-pressure reactor at 180°C and 10MPa for insulation and aging for 12 hours, and then the reactor is taken out and cooled to room temperature, the supernatant is removed, and then the obtained product is rinsed with deionized water to neutrality and filtered, and the filter cake is placed in a vacuum drying oven at 60°C to dry to obtain solid hydrocalumite, and the molar ratio of calcium hydroxide, sodium aluminate and sodium carbonate is 4:2:1;

[0033] S3, preparation of coupled grafted modified hydrocalumite;

[0034] 0.7 g of aluminate coupling agent was added to 10 mL of anhydrous ethanol, and stirred evenly to obtain an aluminate coupling agent solution. Then 10 g of the hydrocalumite prepared above was added to a beaker containing 90 mL of distilled water, stirred with a glass rod and then drained into a three-necked flask. The aluminate coupling agent solution prepared above was added to the three-necked flask, stirred in a 45° C. water bath for 45 min, and then 2.1 g of n-dodecene and 52.5 mg of initiator azobisisobutyronitrile were added to the three-necked flask, heated to 60° C., and reacted for 3 h. After the reaction was completed, ethanol was used as a solvent, purified and extracted with a Soxhlet extractor at 80° C. for 24 h, and then dried at 70° C. to obtain coupling grafted modified hydrocalumite;

[0035] S4. Preparation of environmentally friendly stabilizer;

[0036] The zinc salt main stabilizer, the calcium salt main stabilizer, the zinc oxide-mannitol composite material and the coupled grafted modified hydrocalumite were weighed respectively, ground and mixed for 10 minutes, and then the mixture was placed in a 120° C. oven and baked for 2 hours, and then the mixture was cooled to room temperature to obtain an environmentally friendly stabilizer.

[0037] Example 2 An environmentally friendly stabilizer for PVC foam products comprises the following components by weight: 12 parts of a zinc salt main stabilizer, 38 parts of a calcium salt main stabilizer, 16 parts of a zinc oxide-mannitol composite material, and 34 parts of coupled grafted modified hydrocalumite.

[0038] Example 3 An environmentally friendly stabilizer for PVC foam products comprises the following components by weight: 12 parts of a zinc salt main stabilizer, 42 parts of a calcium salt main stabilizer, 14 parts of a zinc oxide-mannitol composite material, and 32 parts of coupled grafted modified hydrocalumite.

[0039] Example 4 An environmentally friendly stabilizer for PVC foam products comprises the following components by weight: 10 parts of a zinc salt main stabilizer, 42 parts of a calcium salt main stabilizer, 13 parts of a zinc oxide-mannitol composite material, and 35 parts of coupled grafted modified hydrocalumite.

[0040] Example 5 In this example, the initial coloring time and long-term thermal stability time of the environmentally friendly stabilizer prepared in Example 1 were tested by thermal aging experiments.

[0041] 100 g of PVC resin and 4 g of the environmentally friendly stabilizer prepared in Example 1 were mixed evenly, then placed in a double-roll roller press, fully mixed at 180° C. for 5 min, pressed into 2 mm thin sheets, and the prepared thin sheets were cut into 1 cm×1 cm samples, recorded as the experimental group.

[0042] Another 100 g of PVC resin was mixed with 4 g of calcium stearate / zinc composite heat stabilizer, then placed in a double-roll roller press, fully mixed at 180°C for 5 min, pressed into a 2 mm thin sheet, and the prepared thin sheet was cut into 1 cm × 1 cm samples, recorded as the control group. The mass ratio of calcium stearate to zinc stearate in the calcium stearate / zinc composite heat stabilizer was 15:5.

[0043] The control group and experimental group samples were placed on tin foil, put into a heat aging experimental oven, and aged at 180°C. The initial coloring time and complete blackening time of the experimental group and control group samples were recorded. The results are shown in Table 1.

[0044] Table 1 Experimental results of the initial coloring time and long-term thermal stability time determined by the oven method

[0045] Group Initial coloring time / min Complete blackening time / min Control group 15 53 Experimental Group 38 84

[0046] It can be seen from Table 1 that the environmentally friendly stabilizer prepared in Example 1 of the present invention has longer initial coloring time and complete blackening time than ordinary calcium zinc stabilizers, and has good thermal stability.

[0047] Example 6 This example verifies through a melt index analysis experiment that the environmentally friendly stabilizer of the present invention can weaken the cohesive force between PVC macromolecules, reduce the viscosity of the PVC melt, and improve the fluidity of the melt. The specific experimental method is as follows:

[0048] Zinc stearate, calcium stearate, zinc oxide-mannitol composite material and hydrocalumite were weighed respectively, ground and mixed for 10 minutes, and then the mixture was placed in an oven at 120°C and baked for 2 hours. The mixture was then cooled to room temperature to obtain a comparative environmentally friendly stabilizer, wherein each component was measured by weight, namely 11.4 parts of zinc stearate, 40 parts of calcium stearate, 14.3 parts of zinc oxide-mannitol composite material, and 34.3 parts of hydrocalumite.

[0049] 100 g of PVC resin and 4 g of the environmentally friendly stabilizer prepared in Example 1 were mixed evenly to obtain a test sample.

[0050] Another 100 g of PVC resin and 4 g of comparative environmentally friendly stabilizer were mixed evenly to obtain a comparative sample.

[0051] 100 g of PVC resin and 4 g of calcium stearate / zinc composite heat stabilizer were mixed evenly to obtain a control sample.

[0052] Take 5g of test sample, comparison sample and control sample respectively and put them into the barrel of melt flow rate meter. When loading, use hand-held loading rod to compact the sample and expel air as much as possible. Then heat to 220℃ to melt the sample. Extrude the molten sample under 10kg load. Cut the sample after 3s. Weigh the mass of the extruded sample and measure the melt flow rate. The experimental results are shown as follows: Figure 1 shown.

[0053] Depend on Figure 1 It can be seen that the environmentally friendly stabilizer obtained in Example 1 of the present invention can reduce the melt viscosity of PVC and improve the fluidity of the melt. The melt fluidity of the comparative sample and the common calcium stearate / zinc composite heat stabilizer do not significantly improve the melt fluidity of the PVC resin.

[0054] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. Environmentally friendly stabilizer for PVC foam products, characterized in that: By weight, it includes the following components: 10-12 parts of zinc salt main stabilizer, 38-42 parts of calcium salt main stabilizer, 13-16 parts of zinc oxide-mannitol composite material, 32-35 parts of coupled grafted modified hydrocalumite; The zinc oxide-mannitol composite material is a composite of mannitol zinc salt, mannitol and zinc oxide, and the mass ratio of mannitol zinc salt, mannitol and zinc oxide is 37:6:7; The preparation method of the coupled grafted modified hydrocalumite comprises the following steps: adding an aluminate coupling agent to anhydrous ethanol, stirring evenly to obtain an aluminate coupling agent solution, then adding the hydrocalumite to a beaker containing distilled water, stirring with a glass rod and then draining the mixture into a three-necked flask, adding the prepared aluminate coupling agent solution into the three-necked flask, stirring for 45 minutes in a 45° C. water bath, then adding n-dodecene and an initiator azobisisobutyronitrile into the three-necked flask, heating to 60° C., reacting for 3 hours, and after the reaction is completed, using ethanol as a solvent, purifying and extracting with a Soxhlet extractor at 80° C. for 24 hours, and drying at 70° C. to obtain the coupled grafted modified hydrocalumite.

2. The environmentally friendly stabilizer for PVC foam products according to claim 1, characterized in that: By weight, it includes the following components: 11.4 parts of zinc salt main stabilizer, 40 parts of calcium salt main stabilizer, 14.3 parts of zinc oxide-mannitol composite material, and 34.3 parts of coupled grafted modified hydrocalumite.

3. The environmentally friendly stabilizer for PVC foam products according to claim 2, characterized in that: The calcium salt main stabilizer is calcium stearate, and the zinc salt main stabilizer is zinc stearate.

4. The method for preparing the environmentally friendly stabilizer for PVC foam products according to claim 1, characterized in that: The following steps are involved: S1. Preparation of zinc oxide-mannitol composite material; Add zinc oxide and mannitol into a three-necked flask, heat to 200°C in a nitrogen atmosphere, stir and react for 2 hours, take out the product after cooling, and then dry the product in a vacuum oven at 70°C for 12 hours to obtain a zinc oxide-mannitol composite material; S2. Preparation of hydrocalumite: Calcium hydroxide, sodium aluminate and sodium carbonate are used as raw materials and hydrocalumite is prepared by a hydrothermal crystallization method. S3, preparation of coupled grafted modified hydrocalumite; Add an aluminate coupling agent to anhydrous ethanol and stir evenly to obtain an aluminate coupling agent solution, then add the above-prepared hydrocalumite to a beaker filled with distilled water, stir with a glass rod and drain into a three-necked flask, add the above-prepared aluminate coupling agent solution to the three-necked flask, stir in a 45°C water bath for 45 minutes, then add n-dodecene and initiator azobisisobutyronitrile to the three-necked flask, heat to 60°C, react for 3 hours, after the reaction is completed, use ethanol as a solvent, purify and extract with a Soxhlet extractor at 80°C for 24 hours, and dry at 70°C to obtain coupling grafted modified hydrocalumite; S4. Preparation of environmentally friendly stabilizer; The zinc salt main stabilizer, the calcium salt main stabilizer, the zinc oxide-mannitol composite material and the coupled grafted modified hydrocalumite were weighed respectively, ground and mixed for 10 minutes, and then the mixture was placed in a 120° C. oven and baked for 2 hours, and then the mixture was cooled to room temperature to obtain an environmentally friendly stabilizer.

5. The method for preparing an environmentally friendly stabilizer for PVC foam products according to claim 4, characterized in that: In step S1, the molar ratio of zinc oxide to mannitol is 1:

1.

6. The method for preparing an environmentally friendly stabilizer for PVC foam products according to claim 4, characterized in that: In step S2, the specific steps of the hydrothermal crystallization method are: adding calcium hydroxide, sodium aluminate and sodium carbonate in a molar ratio of 4:2:1 to a reactor, adding 180mL of deionized water to the reactor, and then stirring at room temperature for 10 hours, transferring to a 180°C, 10MPa high-pressure reactor for insulation and aging for 12 hours, then taking out the reactor and cooling it to room temperature, removing the supernatant, and then rinsing the obtained product with deionized water to neutrality and filtering, and drying the filter cake in a vacuum drying oven at 60°C to obtain solid hydrocalumite.

7. The method for preparing an environmentally friendly stabilizer for PVC foam products according to claim 4, characterized in that: The usage amount of the aluminate coupling agent is 7% of the mass of hydrocalumite, the mass ratio of n-dodecene to the aluminate coupling agent is 3:1, and the addition amount of the initiator azobisisobutyronitrile is 2.5% of the mass of n-dodecene.

Citation Information

Patent Citations

  • Environment-friendly hydrocalumite-based PVC composite heat stabilizer

    CN109354807A